THE DIFFERENCE IN FINANCIAL LITERACY OF WOMEN WORKERS IN THE FORMAL SECTOR AND THE INFORMAL SECTOR IN THE COMMUNITY IN TOTE VILLAGE - Alimullah, Fadliyah; Mahmud, Melizubaida; Dama, Maya Novrita; Polamolo , Cristian; Hafid, Radia (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to determine the difference in the level of financial literacy between women workers in the formal and informal sectors in the community in Tote Village, West Bolangitang District, North Bolaang Mongondow Regency. Financial literacy is an individual's ability to manage finances which includes aspects of knowledge, attitudes, and skills in making financial decisions. This study uses a quantitative method with a comparative approach. The population in this study is all women who work in the formal and informal sectors in Tote Village, with sampling using purposive sampling techniques. The research instrument is in the form of a questionnaire that is compiled based on financial literacy indicators, then analyzed using a different test (Independent Sample T-Test). The results of the study show that there is a significant difference in the level of financial literacy between women workers in the formal sector and the informal sector. Women in the formal sector tend to have a higher level of financial literacy compared to women working in the informal sector. These findings indicate the importance of more inclusive financial education and training programs, especially for women in the informal sector, to improve financial management skills and support the welfare of families and communities in a sustainable manner.